2016 3rd International Conference on Information Science and Control Engineering (ICISCE) 2016
DOI: 10.1109/icisce.2016.276
|View full text |Cite
|
Sign up to set email alerts
|

Digital Adaptive Carrier Phase Estimation in Multi-level Phase Shift Keying Coherent Optical Communication Systems

Abstract: Copies of full items can be used for personal research or study, educational, or not-for profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way.Publisher's statement: "© 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is demonstrated that an unbiased sinusoidal phase estimator does not exist and estimators with less bias than the maximum likelihood estimator (MLE) have been derived . The analysis of adaptive phase estimation is also important because it is performed in high‐speed n‐level phase‐shift keying optical fiber communication systems using the least mean square algorithm …”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that an unbiased sinusoidal phase estimator does not exist and estimators with less bias than the maximum likelihood estimator (MLE) have been derived . The analysis of adaptive phase estimation is also important because it is performed in high‐speed n‐level phase‐shift keying optical fiber communication systems using the least mean square algorithm …”
Section: Introductionmentioning
confidence: 99%
“…The effects of EEPN have been studied for single-channel, WDM, OFDM, pre-distortion of dispersion, and multi-mode fibre transmission networks [45][46][47][48][49]. Also, research has been implemented to study the performance of EEPN in the CPE in long-haul optical transmission systems [50][51][52][53][54][55][56]. Considering the impact of EEPN, traditional analyses of the CPE algorithms are not appropriate any more for the design of DSP based highcapacity communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Using coherent detection, the powerful compensation of transmission impairments can be implemented in electrical domain. With the full information of the received signals, the chromatic dispersion, the polarization mode dispersion, the carrier phase noise and the fiber Kerr nonlinearities can be equalized and mitigated using digital signal processing (DSP) [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%